Biokomposit Papan Partikel diperkuat Serat Alam Sabut Kelapa dan Tempurung Kelapa dan matriks epoksi - Ginting, Delovita; Syahputra, Romi Fadli; Jannah, Wirdatul (Universitas Muhammadiyah Yogyakarta, 2023)
Natural fiber particle board (biocomposite) can be used as an alternative to conventional materials because it is environmentally friendly, a renewable source and is naturally biodegradable. This research presents a study on the mechanical and physical characterization of natural fiber reinforced polymer particle board, namely coconut coir and coconut shell. The fixed variable in this study was the number of matrix fractions, namely epoch resin. The variable mass fraction of the particle board in this study was coconut coir:coconut shell:epoxy was PP1 (30:0:70), PP2 (22,5:7,5:70), PP3 (15:15:70), PP4 (7,5:22,5:70), and PP5 (0:30:70). Particle board was tested for flexibility using the Universal Testing Machine referring to ASTM D 7-90-03, the impact toughness of the samples using the Impact Tester machine referring to ASTM D 6110. The samples were tested for density and thickness expansion referring to SNI 03-2105-2006. The results of the sample testing showed that the optimum density value for the PP3 sample was 1.05 g/cm3 for the reinforced coconut coir and coconut shell samples. The test results for the optimum impact toughness test value on the PP5 sample were 3.20 J/cm2 and the test results for the optimum flexural strength test value on the PP5 sample were 382.29 Kgf/cm2 with the coconut shell reinforced sample.